Study of New Class of q-Fractional Integral Operator - Momenzadeh, M.; Mahmudov, N. I. (Univ Nis, Fac Sci Math, 2019)
In this paper, we study on the new class of q-fractional integral operator. In the aid of iterated Cauchy integral approach to fractional integral operator, we applied t(p) f(t) in these integrals and a new class of q-fractional integral operator with parameter p, is introduced. Recently, the q-analogue of fractional differential integral operator is studied and all of the operators defined in these studies are q-analogue of Riemann fractional differential operator. We show that our new class of operator generalize all the operators in use, and additionally, it can cover the q-analogue of Hadamard fractional differential operator, as well. Some properties of this operator are investigated.
Keywords: q-fractional differential integral operator; Hadamard fractional differential operator